2016
DOI: 10.1063/1.4950826
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photo/electroluminescence properties of Eu-doped GaN through optimization of the growth temperature and Eu related defect environment

Abstract: The influence of growth temperature on the surface morphology and luminescence properties of Eu-doped GaN layers grown by organometallic vapor phase epitaxy was investigated. By using a Eu source that does not contain oxygen in its molecular structure, and varying the growth temperature, the local defect environment around the Eu3+ ions was manipulated, yielding a higher emission intensity from the Eu3+ ions and a smoother sample surface. The optimal growth temperature was determined to be 960 °C and was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The light is absorbed in GaN and, subsequently, nonradiative recombination of the generated carriers can excite the Eu 3+ ions. The effectiveness of this excitation mechanism is strongly dependent on the local crystal environment of the Eu 3+ ions, and is influenced by defects and strain 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The light is absorbed in GaN and, subsequently, nonradiative recombination of the generated carriers can excite the Eu 3+ ions. The effectiveness of this excitation mechanism is strongly dependent on the local crystal environment of the Eu 3+ ions, and is influenced by defects and strain 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The LT-MLS LED had a significantly higher maximum output power of ~110 µW, compared to 48 µW from the 300nm bulk LED. [9] Again, since the total GaN:Eu layer thickness was a factor of three lower for the LT-MLS LED, this means that the output power per GaN:Eu layer thickness was 5.8 times higher. This promising result indicated that an even higher output power could be achieved by increasing the number of pairs in the LT-MLS LED, as long as the output power scaled with the number of pairs.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, it was found that the use of a new Eu precursor (EuCp pm 2 ) with a lower growth temperature of 960 o C reduced the surface roughness of GaN:Eu samples, and led to an enhancement of the integrated emission intensity. However, the photoluminescence (PL) emission spectra was quite broad, which was attributed to significant variations in the local defect structure around certain Eu ions, which may inhibit their optical activity [9]. A delta doped multilayer structure (MLS) containing 40 pairs of alternating GaN/GaN:Eu was recently shown to significantly increase the emissivity of Eu 3+ ions [10].…”
Section: Introductionmentioning
confidence: 99%
“…[20] The influence of growth temperature on the surface morphology and luminescence properties of Eu-doped GaN layers grown by organometallic vapor phase epitaxy was investigated by Zhu and coworkers. [21] Luminescence properties of defects in thin GaN layers (200µm) are investigated by Reshchikov and coworkers. [22] These defects are supposed to notably affect the electrical and optical properties of the host material and can seriously degrade the performance and reliability of devices.…”
Section: Additional Literature Of Thin Film Doped Ganmentioning
confidence: 99%